Inflation heterogeneity across Austrian households: Evidence from household scanner data - Teresa Messner; Fabio Rumler (European Central Bank (ECB), 2024)
It has been widely documented that households experience different inflation rates which are generally concealed in aggregate price indices. Using scanner data from a large household panel for Austria, we analyse price dynamics faced by individual households and try to explain the causes for the observed inflation differences. Considering not only consumption shares but also the specific product prices paid by households, we find a considerable and persistent degree of heterogeneity among household inflation rates. These are also quite variable over time, resulting from varying consumption baskets and active product substitution, allowing households to reduce their inflation exposure substantially. Factors like age and shopping behavior of households explain some of the inflation differences, whereas income does not seem to have a notable influence in normal times. However, during high inflation periods, the lowest income group is found to face higher inflation rates than other income groups.
Keywords: D12; D30; E31; 330; Household inflation; heterogeneity; micro data